Deamidation of human proteins - Robinson, N. E. (The National Academy of Sciences, 2001)
Deamidation of asparaginyl and glutaminyl residues causes time-dependent changes in charge and conformation of peptides and proteins. Quantitative and experimentally verified predictive calculations of the deamidation rates of 1,371 asparaginyl residues in a representative collection of 126 human proteins have been performed. These rates suggest that deamidation is a biologically relevant phenomenon in a remarkably large percentage of human proteins.